Managing biomass in semi-arid Burkina Faso: Strategies and levers for better crop and livestock production in contrasted farm systems. (August 2022) - Assogba, Gildas G.C.; Adam, Myriam; Berre, David; Descheemaeker, Katrien
Abstract: CONTEXT: The semi-arid zone of Burkina Faso is characterized by strong climate variability and declining soil fertility associated with low biomass production. OBJECTIVE: The main objective of this study was to identify key levers to improve biomass management in semi-arid Burkina Faso for diverse farm types. METHODS: Farm diversity was captured with a statistical typology complemented by a participatory typology established with local farmers. Biomass management was described for the different farm types based on survey information obtained from 228 households across two villages. Fuzzy Cognitive Mapping (FCM) was conducted to represent biomass production strategies of each farm type. After a sensitivity analysis which revealed model robustness, scenario analysis was performed with the FCMs to explore farm type-specific options for alleviating biomass scarcity. Two contrasting scenarios were built based on observations and insights from the survey and focus group discussions with farmers and included (1) deliberate exchange of crop residue with manure, and (2) a subsidies policy allowing a reduction in prices of 30% for farm inputs coupled with increased off-farm revenue for the subsistence-oriented farms. RESULTS AND CONCLUSIONS: The statistical typology identified four farm types, distinguishing between subsistence or market-oriented farms and crop or livestock-oriented production. The participatory typology partly confirmed these four main types, even though other criteria of distinction were given by farmers. Different farm types used contrasted strategies in biomass production and management which were mainly driven by the total cultivated area and the herd size. The farm type with the largest herd and smallest cultivated land was the only one to rely on grain inflow from outside the farm to meet its household food requirement. The inflow of crop residue was also largest for this farm type. In contrast, crop residue outflow was mainly observed for the subsistence-oriented crop farm type, which had the smallest fodder needs. The scenario analysis using FCM suggested that biomass exchange had a negligible effect on farm performance but that the subsidy and income diversification scenario positively impacted crop and livestock production, especially for the subsistence-oriented types. SIGNIFICANCE: Our study pointed out that FCM is a useful tool to not only describe system dynamics but also to reveal levers for improvement through sensitivity and scenario analysis. These levers included income diversification (for subsistence farms especially), improved production and storage of forage (for large herd owners), and investment into equipment and better access to markets (for market-oriented farms). Graphical abstract: Unlabelled Image Highlights: Complementing a statistical typology with a participatory typology increases the legitimacy of a farm diversity assessment. Biomass management strategies differ across farm types and were mainly driven by cultivated area and herd size. Fuzzy Cognitive Mapping was useful for representing and exploring farm-scale biomass management strategies. Key levers for better biomass production include income diversification, investment in equipment and farm type-specific management options. Targeted policies to encourage off-farm employment and improve market access are key to increase biomass production.